Interpretation of single band patterns in CSF protein electrophoresis. - Bass, B; Armstrong, H; Weinshenker, B; Ebers, G; Noseworthy, J; Rice, G (1988)
We have examined the diagnostic significance of finding one band in the immunoglobulin (IgG) region in spinal fluid protein electrophoresis. From January 1983 to January 1986, 855 consecutive CSF electrophoreses were performed on as many patients. A blinded observer identified a single band in the IgG region in 53 cases (6.2%). In only 14 patients (26%), were the clinical features ultimately felt to be due to clinically definite or possible multiple sclerosis (MS). The majority of patients with a single band had another neurological diagnosis (55%) or were neurologically normal (6%). Many of the neurological disorders in which a single band was found were not disorders in which an increased intrathecal synthesis of immunoglobulin or electrophoretic restriction would have been expected. A variety of conditions can produce a single band pattern. The significance of these patterns and the means by which they might be identified are described.